Livelihood Assets in Entikong Village, Sanggau Regency, West Kalimantan - Busono, Woro; Hidayat, Ar Rohman Taufiq; Kurniawan, Eddi Basuki; Perdanasari, Zhuniart Ayu; Hutama, Jatayu Atma; Maylinda, Sucik (International Journal of Social and Local Economic Governance, 2017)
According to NAWACITA (Indonesia’s 9 years long plans), frontier region has priority to be developed because it is characterized as underdeveloped region which has inadequate infrastructures and underprivileged families. The study aims to assess the condition of livelihood assets in the frontier region. Livelihood assets are assets that local people use for living. This research employed descriptive statistical analysis which the data was derived from questionnaire, interview, and observation. Variables to assess the condition of assets were from financial livelihood asset, human asset, social asses, and natural asses. The result is drawn on a pie chart and allowed assets to clearly identify. The results stated that the highest asset is from human asset i.e. sub variable local ecological knowledge ( 85%) which is the knowledge of farming. Therefore, the lowest asset also from human assets i.e. access for education and additional skills. Local people are having difficulties to access the education center just like in Hillbilly Merau and Serangkang because the way to reach there still rocky and rough (undeveloped). Local skills in the village of Entikong are not fully mastered yet but people take special attention in the field of crafts.